Environment-dependent regulation of spliceosome activity by the LSM2-8 complex in Arabidopsis. Issue 12 (8th May 2017) - Carrasco-López, Cristian; Hernández-Verdeja, Tamara; Perea-Resa, Carlos; Abia, David; Catalá, Rafael; Salinas, Julio
Abstract: Spliceosome activity is tightly regulated to ensure adequate splicing in response to internal and external cues. It has been suggested that core components of the spliceosome, such as the snRNPs, would participate in the control of its activity. The experimental indications supporting this proposition, however, remain scarce, and the operating mechanisms poorly understood. Here, we present genetic and molecular evidence demonstrating that the LSM2–8 complex, the protein moiety of the U6 snRNP, regulates the spliceosome activity in Arabidopsis, and that this regulation is controlled by the environmental conditions. Our results show that the complex ensures the efficiency and accuracy of constitutive and alternative splicing of selected pre-mRNAs, depending on the conditions. Moreover, miss-splicing of most targeted pre-mRNAs leads to the generation of nonsense mediated decay signatures, indicating that the LSM2–8 complex also guarantees adequate levels of the corresponding functional transcripts. Interestingly, the selective role of the complex has relevant physiological implications since it is required for adequate plant adaptation to abiotic stresses. These findings unveil an unanticipated function for the LSM2–8 complex that represents a new layer of posttranscriptional regulation in response to external stimuli in eukaryotes.